From strain to strength through humor: resilience in professional football players - Pekel, Aydın; Turan, Mehmet Behzat; Güler, Vesile Şahiner; Iqbal, Mujahid; Pepe, Osman; Arısoy, Abdullah; Dalbudak, İbrahim (Frontiers in Psychology, 2026)
BackgroundAthletes often face competitive stress, with resilience and coping humor as key resources to mitigate its negative impact on mental well-being and performance.ObjectiveThis study aims to examine the relationships between psychological strain, resilience, and coping humor among professional Turkish football players, and to investigate the moderating role of humor-based coping in the link between strain and resilience.MethodThis cross-sectional study involved 466 professional Turkish football players (2024–2025 season). Data were collected via the APSQ, BRS, and CHS, and analyzed using SPSS v22, which included correlations, regressions, and moderation testing with the PROCESS Macro Model 1 (5,000 bootstraps). Additionally, the Jamovi 2.6.2.0 Package program was used.ResultsPsychological strain significantly predicted resilience, and coping humor showed a direct positive effect on resilience. Significantly, coping humor moderated the relationship between strain and resilience, such that the positive association was strongest at high levels of coping humor. Athletes with higher humor-based coping skills were likelier to transform psychological strain into resilience, while the effect was nonsignificant at low humor levels.ConclusionThe findings demonstrate that coping with humor strengthens athletes’ resilience and amplifies the beneficial effects of psychological strain when interpreted as a challenge. Integrating humor-based interventions into psychological training programs may enhance football players’ adaptive coping skills, resilience, and overall mental well-being.